2014
DOI: 10.3928/01477447-20140528-52
|View full text |Cite
|
Sign up to set email alerts
|

Coracoclavicular Ligament Reconstruction: Coracoid Tunnel Diameter Correlates With Failure Risk

Abstract: The current study compared tunnel diameter as an independent risk factor for fixation failure from the coracoid after transcoracoid coracoclavicular reconstruction. The effect of variation in coracoid size and scapular bone density on fixation failure was also studied. Sixty-two cadaveric scapulae were randomized into 1 of 4 groups: a control group with no coracoid hole, a group with a 4-mm transcoracoid tunnel, a group with a 6-mm transcoracoid tunnel, and a group with a socket technique using a 6-mm hole sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Recently, several studies independently showed a significantly increased risk of fracture when large bone tunnels were created in the distal clavicle or coracoid to allow for graft passage. [51][52][53][54][55] Specifically, clavicular bone tunnels of 5 mm or greater in diameter and coracoid bone tunnels of 4 mm or greater in diameter were associated with bony failure. As a result, many surgeons have begun to prepare the distal clavicle and coracoid using bone tunnels with smaller diameters to decrease the risk of fractures.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, several studies independently showed a significantly increased risk of fracture when large bone tunnels were created in the distal clavicle or coracoid to allow for graft passage. [51][52][53][54][55] Specifically, clavicular bone tunnels of 5 mm or greater in diameter and coracoid bone tunnels of 4 mm or greater in diameter were associated with bony failure. As a result, many surgeons have begun to prepare the distal clavicle and coracoid using bone tunnels with smaller diameters to decrease the risk of fractures.…”
Section: Discussionmentioning
confidence: 97%
“…We believe that appropriate visualization of the inferior surface of coracoid process and drilling with a 4-mm drill close to the base of the coracoid is essential. In a cadaveric study, Rylander et al [21] showed that a 4-mm tunnel technique is significantly stronger than a 6-mm tunnel technique when using a transcoracoid reconstruction technique. In addition, tunnel placement is also a significant factor to avoid coracoid fractures and failure of fixation.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that appropriate visualization of the inferior surface of coracoid process and drilling with a 4mm drill close to the base of the coracoid is essential. In a cadaveric study, Rylander et al [21] showed that a 4-mm tunnel technique is significantly stronger than a 6-mm tunnel technique when using a transcoracoid reconstruction technique. In addition, tunnel placement is also a significant factor to avoid coracoid fractures and failure of fixation.…”
Section: Discussionmentioning
confidence: 99%